Functional bowel symptoms in diabetes--the role of autonomic neuropathy. - Maxton, D. G. (BMJ Group, 1991)
The autonomic nervous system may have a role in the pathogenesis of irritable bowel syndrome. If so, the occurrence of irritable bowel symptomatology in patients with autonomic neuropathy might indicate which, if any, of these symptoms are dependent on autonomic innervation. The prevalence of abdominal pain, abdominal distension and an abnormal bowel habit was recorded in 200 patients with diabetes, screened for autonomic neuropathy, and 200 matched controls. Constipation was significantly more common in patients with autonomic neuropathy than in those without, or controls (22.0% vs 9.2% vs 6.8%). The prevalence of abdominal pain and abdominal distension was no different in patients with and without autonomic neuropathy and their respective controls. The results of this study suggest that control of bowel habit is more dependent on the total integrity of the autonomic nervous system than the perception of pain or the production of distension.